The Chocoan Dimension of the Liga Costeña: Region, Centralism and Autonomy in Colombia at the Beginning of the 20th century - Flórez-Bolívar, Francisco Javier; Rhenals-Doria, Ana Milena; Flórez-Bolívar, Roicer Alberto (Sociedad y Economía, 2023)
This article examines how Chocó, a region in the Pacific coast of Colombia, became part of the Liga Costeña, a regional initiative led by businessmen and politicians from the Colombian Caribbean between 1918 and 1920. The methodology used is based on recent approaches to regional studies, especially those that emphasize the importance of conceiving regions as spaces shaped by the movement of people and ideas. The main conclusion is that Chocó’s inclusion in the Liga Costeña was motivated by two factors: first, the historical ties that existed between the inhabitants of both regions; and second, the common interest in finding a solution to the negative effects of the centralization process of the Colombian State on Chocó and the Caribbean coast in the early 20th century.